PENGARUH RETURN SAHAM, VOLUME PERDAGANGAN SAHAM, DAN VOLATILITAS HARGA SAHAM TERHADAP BID ASK SPREAD (Studi Empiris pada Industri Pertambangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2021) - Novita Yuli Lubis; Wilda Sri Munawaroh Hrp (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2022)
This study aims to determine the effect of stock returns, trading volume and stock price volatility on the bid ask spread of mining companies listed on the Indonesia Stock Exchange in 2017-2021. This research is an associative type of research. The sampling technique was carried out using a purposive sampling technique. So that the sample obtained is 8 mining companies listed on the IDX in 2017 - 2021 with a total of 50 observational data for 5 years of observation. The data collection technique used is documentation. The data analysis technique used in this research is linear regression analysis of panel data using eviews. The results of the stock return research show that the results have no effect on the bid ask spread. Trading volume has an effect on the bid ask spread. The results of the research on stock price volatility show that the results have no effect on the bid ask spread. The results of the research on stock returns, trading volume and stock price volatility simultaneously show that there is an effect on the bid ask spread.